Smart AI-Enabled SAK EMKM for Accounting Transformation and MSME Financial Performance - Nurul Alfiyah; Indira Nuansa Ratri; Lukman Hakim; Sari Wiji Utami (Invoice : Jurnal Ilmu Akuntansi, 2026)
This study examines how artificial intelligence (AI)-enabled digital accounting platforms support the implementation of Financial Accounting Standards for Micro, Small, and Medium Entities (SAK EMKM) while improving the financial performance and governance of MSMEs. Although standardized financial reporting is increasingly essential for business sustainability and regulatory compliance, many MSMEs continue to depend on manual bookkeeping systems that hinder reporting accuracy, timeliness, and decision usefulness. Addressing this gap, the study investigates the digital accounting transformation of Batik Muktiyasa, a batik MSME in Banyuwangi, Indonesia, through a qualitative contextual approach combined with action research. Data were obtained through interviews, direct observation, financial document analysis, and system implementation to compare accounting practices before and after the adoption of an AI-enabled accounting platform. The findings indicate that AI-based accounting systems not only improve the accuracy of financial records, automate transaction classification, and produce financial statements aligned with SAK EMKM, but also expand the managerial value of accounting information through automated ratio analysis, financial trend detection, and cost-efficiency evaluation. A significant finding is the improvement in accounting compliance from 21.4% before digitalization to full compliance after implementation. The novelty of this research lies in its integration of AI adoption, MSME accounting digitalization, and SAK EMKM compliance within a single contextual transformation framework. The study contributes to the literature by proposing an integrated AI–SAK EMKM accounting transformation model that explains how AI-enabled systems can bridge the gap between informal bookkeeping practices and formal financial reporting standards in MSMEs. Practically, the study provides an applicable model for MSMEs, policymakers, and digital accounting service providers to strengthen financial governance, enhance compliance, and support long-term business sustainability.